2020
DOI: 10.1038/s41598-020-62569-9
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Inertial Microfluidic Devices

Abstract: Inertial microfluidics has been broadly investigated, resulting in the development of various applications, mainly for particle or cell separation. Lateral migrations of these particles within a microchannel strictly depend on the channel design and its cross-section. Nonetheless, the fabrication of these microchannels is a continuous challenging issue for the microfluidic community, where the most studied channel cross-sections are limited to only rectangular and more recently trapezoidal microchannels. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(84 citation statements)
references
References 74 publications
(87 reference statements)
1
74
0
Order By: Relevance
“…3D printing is a versatile fabrication technique that deposits material into three-dimensional space. This allows for the formation of microfluidic structures that are difficult to fabricate with standard photolithography such as rounded cross-section or complex curvilinear microchannels 16 , 17 and adapters to commonly used connection ports such as luer locks 18 and O-ring seals 19 . This technology has many other attractive features for microfluidics 20 22 , including its ability to print biocompatible plastics 20 , hydrogels, live cells 23 , metals 24 , sugars 25 , glass 26 , its simple integration with analytical chemistry modalities 27 , and its ability to iteratively update complex prototypes without the need for photomasks.…”
Section: Introductionmentioning
confidence: 99%
“…3D printing is a versatile fabrication technique that deposits material into three-dimensional space. This allows for the formation of microfluidic structures that are difficult to fabricate with standard photolithography such as rounded cross-section or complex curvilinear microchannels 16 , 17 and adapters to commonly used connection ports such as luer locks 18 and O-ring seals 19 . This technology has many other attractive features for microfluidics 20 22 , including its ability to print biocompatible plastics 20 , hydrogels, live cells 23 , metals 24 , sugars 25 , glass 26 , its simple integration with analytical chemistry modalities 27 , and its ability to iteratively update complex prototypes without the need for photomasks.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent resin drainage issues, Büttner et al demonstrated a single layer exposure method based on DLP projection for printing complex channels with heights of 25-150 µm on polymethyl methacrylate (PMMA) or glass substrates [46]. Another recent work on manufacturability of microfluidics with DLP SLA was demonstrated by Bazaz et al [50]. The group printed open channel microfluidic parts which were then bonded on PMMA sheets with pressure sensitive tape.…”
Section: Manufacturability Of Microfluidic Channels With Stereolithogmentioning
confidence: 99%
“…However, similar approaches with sacrificial material has not been seen for the lower-cost DLP SLA. Different approaches to print enclosed microfluidics with DLP SLA [46,50,51] have produced successful results in their field of applications, however the main drawback lies on the use of adhesives sheets that introduce material inconsistency in the channels and impose multi-step processing.…”
Section: Manufacturability Of Microfluidic Channels With Stereolithogmentioning
confidence: 99%
“…When flowing through a straight rectangular microchannel, initially random suspensions of particles reach certain equilibrium positions. In certain Re, these equilibrium positions are parallel to each other and the adjacent walls [31,32]. Spontaneous lateral migration of particles in Poiseuille flow and finite channel Re arises from a balance between dominant lift forces (F L ), including shear-gradient-induced lift force (F S ), and wall induced lift force (F W ) which are orthogonal to the flow directions [33].…”
Section: Design Principlementioning
confidence: 99%